2012
DOI: 10.1038/mtna.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Delivery of Short Interfering RNA in Rat Organ of Corti Using a Cell-penetrating Peptide PepFect6

Abstract: RNA interference (RNAi) using short interfering RNA (siRNA) is an attractive therapeutic approach for treatment of dominant-negative mutations. Some rare missense dominant-negative mutations lead to congenital-hearing impairments. A variety of viral vectors have been tested with variable efficacy for modulating gene expression in inner ear. However, there is concern regarding their safety for clinical use. Here, we report a novel cell-penetrating peptide (CPP)-based nonviral approach for delivering siRNA into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…PF6 and NF70 have both been previously shown to efficiently induce RNA interference after oligonucleotide delivery in in vitro and in vivo conditions [ 14 , 16 ]. PF6 has been extensively studied and its efficacy has also been shown in primary and 3D organotypic cultures [ 41 ]. NF70, on the other hand, is a novel peptide, with most recent findings showing it can successfully deliver therapeutic miRNA into primary human keratinocytes and dendritic cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…PF6 and NF70 have both been previously shown to efficiently induce RNA interference after oligonucleotide delivery in in vitro and in vivo conditions [ 14 , 16 ]. PF6 has been extensively studied and its efficacy has also been shown in primary and 3D organotypic cultures [ 41 ]. NF70, on the other hand, is a novel peptide, with most recent findings showing it can successfully deliver therapeutic miRNA into primary human keratinocytes and dendritic cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…They gain access to the cell interior mainly by endocytosis, and thus have the capacity to promote intracellular delivery of conjugated bioactive cargo (151). Dash-Wagh et al (80) tested the efficiency of a novel cell-penetrating peptide, PepFect6 (PF6), to deliver connexin 26 siRNA into the cochlear cells in vitro. They showed that PF6 was internalized by all cells in cochlear cultures without inducing cytotoxicity, and led to the knockdown of both connexin 26 and 30 mRNA in cochlear cells.…”
Section: Nonviral Vectorsmentioning
confidence: 99%
“…CPPs can transport to the inside of cells while carrying a wide variety of covalently or noncovalently linked cargo, including nanoparticles, peptides, proteins, antisense oligonucleotides, small-interfering RNA, double-stranded DNA, and liposomes. , Interestingly, preclinical evaluations of CPP-derived therapeutics showed promising results in various disease models, which subsequently translated into clinical trials . Therefore, CPPs represent an effective approach for delivering bioactive molecules into cells for various biomedical applications. , …”
Section: Introductionmentioning
confidence: 99%